Carbene organic catalytic planar enantioselective macrolactonization - Lv, Xiaokang (2024)
Macrolactones exhibit distinct conformational and configurational properties and are widely found in natural products, medicines, and agrochemicals. Up to now, the major effort for macrolactonization is directed toward identifying suitable carboxylic acid/alcohol coupling reagents to address the challenges associated with macrocyclization, wherein the stereochemistry of products is usually controlled by the substrate's inherent chirality. It remains largely unexplored in using catalysts to govern both macrolactone formation and stereochemical control. Here, we disclose a non-enzymatic organocatalytic approach to construct macrolactones bearing chiral planes from achiral substrates. Our strategy utilizes N-heterocyclic carbene (NHC) as a potent acylation catalyst that simultaneously mediates the macrocyclization and controls planar chirality during the catalytic process. Macrolactones varying in ring sizes from sixteen to twenty members are obtained with good-to-excellent yields and enantiomeric ratios. Our study shall open new avenues in accessing macrolactones with various stereogenic elements and ring structures by using readily available small-molecule catalysts.